2011
DOI: 10.1021/ed100337a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplemental Instruction in Entry-Level Chemistry Courses at a Midsized Public University

Abstract: This paper examines the impact of supplemental instruction (SI)nonremedial workshops that support regularly scheduled courseson four different chemistry courses: General Chemistry I and II, and Organic Chemistry I and II. Differences in how SI impacts student performance in these courses are discussed, particularly in terms of whether students from underrepresented minority groups are affected differently from their peers. We found that SI appears to be most effective in courses at the beginning of the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Additionally, several authors have attempted to assess the relative independent contribution of academic preparedness and/or prior academic achievement in predicting academic performance (multiple regression). Although Fjortoft et al () reported that SI attendance was not a significant predictor of academic performance, several authors have found SI attendance to be a positive predictor (Fayowski and MacMillan, ; Oja, ; Rath et al, ). Studies have also found that aptitude test scores, high school grades, and prior post‐secondary grades were positive predictors of academic performance (Fjortoft et al, ; Fayowski and MacMillan, ; Oja, ; Rath et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, several authors have attempted to assess the relative independent contribution of academic preparedness and/or prior academic achievement in predicting academic performance (multiple regression). Although Fjortoft et al () reported that SI attendance was not a significant predictor of academic performance, several authors have found SI attendance to be a positive predictor (Fayowski and MacMillan, ; Oja, ; Rath et al, ). Studies have also found that aptitude test scores, high school grades, and prior post‐secondary grades were positive predictors of academic performance (Fjortoft et al, ; Fayowski and MacMillan, ; Oja, ; Rath et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Fjortoft et al () reported that SI attendance was not a significant predictor of academic performance, several authors have found SI attendance to be a positive predictor (Fayowski and MacMillan, ; Oja, ; Rath et al, ). Studies have also found that aptitude test scores, high school grades, and prior post‐secondary grades were positive predictors of academic performance (Fjortoft et al, ; Fayowski and MacMillan, ; Oja, ; Rath et al, ). However, McCarthy et al () have suggested that since typical measures of academic preparedness (e.g., AGPA) may not be reliable predictors of academic success at university, alternative measures of a student's “academic ability in the university environment” (e.g., aggregate grade of all common courses completed by the students in the course) should be used in analyses of SI effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is applied to make predictions of the dependent variable from one or more independent variables. For instance, Rath et al (13) used linear regression to explore how variables such as high school GPA and SAT scores contributed to university students' final grades in chemistry courses. In a study of examining gender differences in mental rotation tasks of chemistry representations, Stieff (14) used linear regression models to investigate the relationship between response time and angular disparity in two rotation tests.…”
Section: Regressionsmentioning
confidence: 99%